Caregiver Burden and Family Autonomy in Long-Term Elderly Care: A Correlational Study - Adiratna, Brillian Yunita; Melizza, Nur; Budiarti, Nadin; Yossi, Suyesti; Surya, Berlyan; Hermanto, Roby Putra (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
The increasing number of elderly people in Indonesia poses a major challenge in the provision of long-term care services. The elderly tend to experience a decline in physical and mental function so that they depend on the family as the main caregiver. However, the role as a caregiver can cause psychological, physical, economic, and social burdens known as caregiver burden.The purpose of this study was to analyze the relationship between caregiver burden and family independence in long-term care of the elderly.This study used a quantitative approach with a cross-sectional design, conducted from September 2024 to May 2025 in Malang City. A total of 59 family members who care for the elderly were selected through accidental sampling technique. The instruments used were the Zarit Burden Interview and the Family Independence Level questionnaire. Data analysis was performed with the Spearman Rank test using SPSS version 25.0.  The majority of respondents came from large families (71%) and were female (90%). Most families showed high independence (KM 4), while caregiver burden was classified as mild to moderate. Statistical analysis showed no significant relationship between caregiver burden and family independence (p = 0.741; r = -0.044). Although some caregivers experienced burden, families were still able to care for the elderly independently. Caregiver burden is not the only factor that influences family independence and quality in providing services and long-term care for the elderly. Emotional support, family togetherness, and cultural values are thought to play a role in maintaining family independence.